Integrated metabolomic and transcriptomic analyses reveal different metabolite biosynthesis profiles of Juglans mandshurica in shade - Zhang, Xinxin; Li, Yuxi; Yan, Huiling; Cai, Kewei; Li, Hanxi; Wu, Zhiwei; Wu, Jianguo; Yang, Xiangdong; Jiang, Haichen; Wang, Qingcheng; Qu, Guanzheng; Zhao, Xiyang (Frontiers in Plant Science, 2022)
Light is not only a very important source of energy for the normal growth and development of plants, but also a regulator of many development and metabolic processes. The mechanism of plant growth and development under low light conditions is an important scientific question. With the promulgation of the law to stop natural forest cutting, understory regeneration is an important method for artificial forest afforestation. Here, the growth and physiological indexes of J. mandshurica, an important hardwood species in Northeast China, were measured under different shade treatments. In addition, transcriptome and metabolome were compared to analyze the molecular mechanism of shade tolerance in J. mandshurica. The results showed that the seedling height of the shade treatment group was significantly higher than that of the control group, and the 50% light (L50) treatment was the highest. Compared with the control group, the contents of gibberellin, abscisic acid, brassinolide, chlorophyll a, and chlorophyll b in all shade treatments were significantly higher. However, the net photosynthetic rate and water use efficiency decreased with increasing shade. Furthermore, the transcriptome identified thousands of differentially expressed genes in three samples. Using enrichment analysis, we found that most of the differentially expressed genes were enriched in photosynthesis, plant hormone signal transduction and chlorophyll synthesis pathways, and the expression levels of many genes encoding transcription factors were also changed. In addition, analysis of differentially accumulated metabolites showed that a total of 470 differential metabolites were identified, and flavonoids were the major differential metabolites of J. mandshurica under light stress. These results improved our understanding of the molecular mechanism and metabolite accumulation under light stress in J. mandshurica.